Decoding the Cornea-Glaucoma Association: Evidence From Mendelian Randomization - de Vries, Victor A; Szabo, Anita; Vergroesen, Joëlle E; Liu, Siyin; van Garderen, Karin A; Muthusamy, Kirithika; Liskova, Petra; Dudakova, Lubica; Khawaja, Anthony P; Tuft, Stephen J; Klaver, Caroline C W; Davidson, Alice E; et al. (Investigative ophthalmology & visual science, 2025)
PURPOSE: We combined classical association analyses with one-sample and two-sample Mendelian randomization (MR), to comprehensively assess the causal relation among central corneal thickness (CCT), corneal hysteresis, Fuchs endothelial corneal dystrophy (FECD), and open-angle glaucoma (OAG). METHODS: We analyzed data from a large population-based cohort study (the Rotterdam Study), an FECD case-control study, and genome wide association study summary statistics. We defined OAG as reproducible visual field loss, independent of IOP. Multivariable regression was performed. One-sample MR was performed using the same regression models, with the corresponding genetic risk score (GRS) as independent variable. Two-sample MR was performed using inverse variance weighted, MR Egger, weighted median, simple mode, and weighted mode methods. RESULTS: In total, 303 participants with OAG and 10,598 controls from the Rotterdam Study were included, with 753 FECD cases from the FECD cohort. The odds ratio (OR) 95% confidence interval (CI) of OAG was 0.67 (95% CI = 0.56-0.81) per standard deviation (SD) increase in CCT (P < 0.001). However, one-sample MR showed no significant association between a CCT-GRS and OAG (P = 0.688). Two-sample MR found an OR (95% CI) of 1.23 (95% CI = 1.06-1.42) for each SD increase in the CCT instrumental variable. We observed no association between an FECD-GRS and OAG (P = 0.946). CONCLUSIONS: We found no evidence for a causal link between CCT and OAG. Nevertheless, CCT measurements are still valuable for population-based risk stratification. We found no clear relationship between FECD and OAG.
Keywords: senioři; celogenomová asociační studie; Glaucoma, Open-Angle; jednonukleotidový polymorfismus; rohovka; Intraocular Pressure; Middle Aged; nitrooční tlak; mužské pohlaví; studie případů a kontrol; zraková pole; Mendelian Randomization Analysis; Fuchs' Endothelial Dystrophy; ženské pohlaví; mendelovská randomizace; Humans; Visual Fields; lidé středního věku; glaukom s otevřeným úhlem; rizikové faktory; Case-Control Studies; Female; Aged; Risk Factors; Genome-Wide Association Study; Fuchsova endoteliální dystrofie; Cornea; lidé; Male; Polymorphism, Single Nucleotide